Advances of Electroactive Metal–Organic Frameworks. Issue 15 (11th January 2023) - Cong, Cong; Ma, Huaibo
Abstract: The preparation of electroactive metal–organic frameworks (MOFs) for applications of supercapacitors and batteries has received much attention and remarkable progress during the past few years. MOF‐based materials including pristine MOFs, hybrid MOFs or MOF composites, and MOF derivatives are well designed by a combination of organic linkers (e.g., carboxylic acids, conjugated aromatic phenols/thiols, conjugated aromatic amines, and N ‐heterocyclic donors) and metal salts to construct predictable structures with appropriate properties. This review will focus on construction strategies of pristine MOFs and hybrid MOFs as anodes, cathodes, separators, and electrolytes in supercapacitors and batteries. Descriptions and discussions follow categories of electrochemical double‐layer capacitors (EDLCs), pseudocapacitors (PSCs), and hybrid supercapacitors (HSCs) for supercapacitors. In contrast, Li‐ion batteries (LIBs), Lithium‐sulfur batteries (LSBs), Lithium‐oxygen batteries (LOBs), Sodium‐ion batteries (SIBs), Sodium‐sulfur batteries (SSBs), Zinc‐ion batteries (ZIBs), Zinc–air batteries (ZABs), Aluminum‐sulfur batteries (ASBs), and others (e.g., LiSe, NiZn, H +, alkaline, organic, and redox flow batteries) are categorized for batteries. Abstract : Increased demand for alleviation of climate change and energy crisis stimulates fast development of energy storage devices such as supercapacitors and batteries, which have virtues of convenience, reusability, and reliability. In this review, the very recent progress on electroactive metal–organic frameworks for supercapacitors and batteries with a particular focus on construction strategies are summarized and discussed.